الانتشار الطبيعي لذبابة الهالوك. Phytomyza orobanchia Kalt على الهالوك المتفرع Orobanche ramosa L. الذي يصيب الباذنجان ودورها المحتمل في المكافحة الحيوية (Latakia University Journal -Biological Sciences Series, 2018)
أجري مسح للعديد من الحقول الزراعية المزروعة بالباذنجان في الساحل السوري، خلال المواسم الزراعية 2003/2002، 2005/2004 و 2006/2005. بهدف تحديد مناطق انتشار الهالوك المتفرع Orobanche ramosa L. وذبابة الهالوك Phytomyza orobanchia Kalt. جمعت عينات عشوائية من نباتات الهالوك المتفرع من الحقول المصابة، وفحصت عن طريق تشريح الأفرع والكبسولات. وأشارت النتائج إلى انتشاره في حقول الباذنجان (Solanum melongena L.)، وانتشار ذبابة الهالوك طبيعياً في هذه الحقول بنسب إصابة مختلفة من موسم لآخر ومن حقل لآخر على الأفرع والكبسولات الثمرية. وكانت أعلى نسبة مئوية للإصابة في الهيشة (طرطوس) حيث وصلت إلى 77.87%. وجد أن معظم الكبسولات المصابة تحتوي على يرقة واحدة وكانت نسبتها 97.03%، بينما بلغت النسبة المئوية للكبسولات المحتوية على يرقتين 2.21% فقط. كما خفضت تغذية يرقات الذبابة من الأوزان الجافة والرطبة للكبسولات والأفرع المصابة مقارنةً مع السليمة. وهذا يشير إلى إمكانية استخدامها في المكافحة الحيوية للهالوك المتفرع. A survey of many fields of eggplant along the Syrian coast was conducted during 2002/2003, 2004/2005 and 2005/2006 growing seasons in order to determine the distribution of branched broomrape (Orobanche ramosa L.) and Phytomyza orobanchia Kalt. Branched broomrape (O. ramosa) plant samples were randomly collected from infested fields; these samples were inspected by dissection of shoots and fruit capsules of O. ramosa. Results of this study showed that the O. ramosa is distributed in eggplant fields and the P. orobanchia is distributed naturally in these fields with different rates of infestation on fruit capsules and shoots. These rates were different from one season to another and from one field to another. The higher rate of infestation was in Alheesha (Tartous) where it reached up to 77.87%, and most numbers of infected capsules contained one larvae. Their rate reached up to 97.03%, while infected capsules which contained two larvae were only 2.21%. Feeding of P. orobanchia larvae in O. ramosa capsules and shoots caused reduction in dry and wet weights of infected shoots and capsules in comparison with healthy shoots and capsules. These results indicate to possibility of using P. orobanchia. in biological control .